Evaluasi Pelaksanaan Program Penguatan Pendidikan Karakter Berbasis Model CIPP di SDN Percobaan Palangka Raya - Pradana Din Permadi; Nani Setiawati; Irfiana Rohmatin (JURNAL PENDIDIKAN, 2026)
Abstract This study purpose to determine: (1) the basis of the policy and the suitability of the program objectives; (2) teacher characteristics; (3) facilitator characteristics; (4) characteristics of the mentoring program; (5) characteristics of infrastructure; (6) mentoring process; (7) PPK based on school culture at SDN Pengalaman Palangkaraya after implementing the PPK program. The results of this study will be able to measure the progress of the implementation of the PPK program at the school, the excavation of data and information about the implementation of the results of the PPK program at SDN Pengalaman Palangkaraya in the implementation of direct assistance funds, and the detection of various problems that can hinder the smooth implementation of the PPK program so that fast and accurate solutions can be achieved. The evaluation research design refers to the CIPP (Context, Input, Process, Product) evaluation model. This design is a framework for the process of carrying out evaluations and plans to collect and utilize data so that sufficient precision can be obtained or hypotheses can be tested appropriately and evaluation objectives can be achieved. Based on the calculation results of the main PPK values, it is known that the PPK values ​​show very significant results starting from the religious character value of 78.9%, the nationalist character value reflecting love for the Republic of Indonesia of 80%, the independent character value of 80%, the mutual cooperation character value of 84%. The integrity character value of 84%. These results indicate that the implementation of PPK values ​​at SDN Pengalaman Palangkaraya was successful.